FRAMING OF MANGROVE CONSERVATION IN THE EASTERN COAST OF SUMATRA: ECOLINGUISTICS STUDY - Muhammad Kiki Wardana; Hidayati Hidayati (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This research aims to investigate the framing encapsulated in the news about mangrove conservation in the eastern coast of Sumatra. The research is important to shape public perception about mangrove because language plays a crucial role in shaping and influencing the general public. This research is also salient to raise the awareness and education about mangrove through ecolinguistics perspective. This research applied qualitative research and used grounded theory approach. The results of this research revealed that there are some frequent framings about mangrove conservation such as ecological framing, social and cultural framing, conservation framing, political and economic framing, and climate change framing